Well-rounded lattices via polynomials with real roots - Alves, Carina [UNESP]; Pinto, William L.S. [UNESP]; Andrade, Antonio A. [UNESP] (Academic Publications, 2020)
Well-rounded lattices have been a topic of recent studies with applications in wiretap channels and in cryptography. A lattice of full rank in Euclidean space is called well-rounded if its set of minimal vectors spans the whole space. In this paper, we investigate the well-roundedness of lattices coming from polynomials with integer coefficients and real roots.
Keywords: Dense packing; Minimum norm; Polynomials; Well-rounded lattice